KEGIATAN FUN KEMERDEKAAN 17 AGUSTUS BAGI ANAK-ANAK PANTI ASUHAN GRAHA YATIM DAN DHU'AFA (GRAY) YAYASAN HARAPAN ROBBANI - Magdalena, Lena; Hatta, Muhammad (Jurnal Pemberdayaan Masyarakat dan Inovasi, 2024)
The activity "Fun Independence Day on August 17 for Children of Graha Yatim and Dhu'afa Orphanage (GRAY) under the Hope Robbani Foundation" is a community service program aimed at providing valuable and festive experiences in celebrating Indonesia's Independence Day for children residing at the Graha Yatim and Dhu'afa Orphanage managed by the Hope Robbani Foundation. This activity is held to instill a sense of nationalism and love for the homeland from a young age, and to create memorable moments for children who may not have had the opportunity to fully celebrate independence. The event will involve the Association of Information Systems Student (Himasi) and several lecturers. The planned series of activities include various enjoyable and educational events, such as marbles competitions, cracker-eating contests, balloon-blowing, traditional Indonesian games, as well as the distribution of small prizes to children as a token of appreciation for their participation. In addition to the celebratory activities, this event will also encompass educational sessions with the aim of enhancing the children's understanding of the significance of Indonesia's Independence Day on August 17 and the nation's struggle to attain freedom. Through storytelling, presentations, and interactive games, the children will be introduced to national hero figures and pivotal moments in Indonesia's history. This initiative serves as a small yet meaningful step in building a foundation of patriotism and communal values among the young generation of Indonesia, and actively contributes to fostering positive community development through dedicated service.